Kampanye Sekolah Sehat di SD 16/IV Kota Jambi - Butar Butar, Marta; Wardiah, Rizalia; Meinarisa, Meinarisa; Nasution, Riska Amalya; Rini, Willia Novita Eka (Prodi Ilmu Kesehatan Masyarakat, FKIK Universitas Jambi, 2024)
The population in the category of children with health complaints in the last month aged 0-4 years is 33.77%, aged 5-9 years is 30.85%, and aged 10-14 years is 25.48% based on BPS data in 2022. (1) Students with unhealthy behavior or chronic conditions may be absent from school more often, reducing their time to study. Improving eating patterns and physical activity is very important, especially for students who have an increased risk of chronic diseases due to their race, ethnicity, or family income level (2) In connection with the high risk of these health problems in students' lives, activities are needed to educate elementary school students to get used to a healthy lifestyle in the school environment as early as possible. The purpose of this activity is to increase knowledge of the 3 S (Healthy Nutritious, Healthy Physically and Healthy Immunization) so that participants can understand and are motivated to carry it out as part of the Healthy School Movement. The method used is a nutritious food campaign such as breakfast and healthy snacks, introducing students to various types of traditional games in order to increase physical activity, and educating the importance of complete immunization in elementary school children. Community service will be carried out by 5 lecturers and 5 students with a target of 40 students. Based on the Wilcoxon T-Test on Pre-test and Post-Test respondents, the results of data testing show a p value = 0.001, it can be concluded statistically that there is a significant difference in knowledge between knowledge before and after the intervention. The output of this community service will be in the form of publications in National journals with ISSN, publications in print media, video documents of activities and cooperation documents in the form of memorandums of agreement (MoA) / cooperation agreements with partners.